Noah - Munowitz, Ken; Mee, Charles L. (New York [u.a.] Harper & Row, 1978)
Retells the story of how Noah and his family built the ark and saved the animals from the Great Flood
Keywords: Noah's Ark -- Juvenile literature; Kinderbuch